SCREENING FOR DIABETIC RETINOPATHY: A COMPARATIVE STUDY BETWEEN HOSPITAL AND COMMUNITY BASED SCREENING AND BETWEEN PAYING AND NON-PAYING PATIENTS - Afghani, Tayyab; Qureshi, Nadeem; Chaudhry, Khalid Saeed Ahmad (Journal of Ayub Medical College Abbottabad, 2007)
Background: Prevalence of diabetes and diabetic retinopathy varies in the population considering the background and financial status. Methods: A total of 79,194 people more than 40 years, were screened for diabetes both in the community and eye hospital setting. Initial screening was carried out by urine dipstick followed by random blood sugar examination. A value ³ 140 mg/dl of blood sugar was considered positive for diabetes. All the diabetics were then examined for any evidence of diabetic retinopathy through indirect ophthalmoscopy in a dilated pupil by a midlevel ophthalmologist. Health education campaign at public, patient and professional level was also conducted. Results: The results of screening were analyzed for three distinct groups; rural population, hospital based free patients and hospital based paying patients. The prevalence of diabetes was found to be 9.12%, 10.34% and 18.57% in rural community, poor hospital and affluent hospital groups respectively. The prevalence of diabetic retinopathy in the total screened population in these three subgroups was 1.92%, 2.52% and 4.42% respectively, while this prevalence in the diabetic population was 21.05%, 24.39% and 23.80% respectively. The cost per person screened was $2.6-3.4, while the cost per diabetic identified was $26-28 and the cost per patient of diabetic retinopathy identified was $ 108-135. Conclusion; The prevalence of diabetic retinopathy was two times more in the affluent hospital patients as compared to poor hospital patients or rural population. For each known diabetic, there were four previously undiscovered diabetics in the rural population, and two previously undiscovered diabetics in hospital based population. Key words: Diabetes Mellitus, Diabetic Retinopathy, Health Education.